Multicultural Education Development; Phylosophy And Implementation - Yaqin, M. Ainul (Jurnal Pendidikan Islam, 2013)
The discussion over the idea of multicultural education has never been finished. Multicultural education is an Educational Philosophy and Practical Educational Strategy that has been well developed in United States. It has been being developed in some countries, and so is Indonesia. The American schools have been developed and implemented the idea of multicultural education and the American government has supported them by giving multicultural values on education policies. In some Indonesian schools, it has also been tried to apply multicultural education, but there are some problems in developing and implementing it, because of the lack of experience in it and the supports from government.